2012
DOI: 10.3390/ijms14010205
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Functional Studies on the Noncoding RNA, PRINS

Abstract: PRINS, a noncoding RNA identified earlier by our research group, contributes to psoriasis susceptibility and cellular stress response. We have now studied the cellular and histological distribution of PRINS by using in situ hybridization and demonstrated variable expressions in different human tissues and a consistent staining pattern in epidermal keratinocytes and in vitro cultured keratinocytes. To identify the cellular function(s) of PRINS, we searched for a direct interacting partner(s) of this stress-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 51 publications
2
47
2
Order By: Relevance
“…Psoriasis is another autoimmune disorder generally thought to be a genetic disease triggered by environmental factors. PRINS (psoriasis susceptibility-related RNA gene induced by stress) is a lncRNA that may contribute to the psoriasis susceptibility [86, 87]. …”
Section: Lncrnas Cancer and Other Diseasementioning
confidence: 99%
“…Psoriasis is another autoimmune disorder generally thought to be a genetic disease triggered by environmental factors. PRINS (psoriasis susceptibility-related RNA gene induced by stress) is a lncRNA that may contribute to the psoriasis susceptibility [86, 87]. …”
Section: Lncrnas Cancer and Other Diseasementioning
confidence: 99%
“…Our results suggest that the overexpression of PRINS in the non-involved psoriatic epidermis may play role in psoriasis susceptibility [37] and are in accordance with previous studies that in response to external stress stimuli, the keratinocytes of the non-involved psoriatic and of the healthy epidermis answer differentially [182,183]. We additionally showed that the expression of the anti-apoptotic G1P3 gene is under the contol of PRINS [148] and PRINS might interact physically with the molecular chaperone protein nucleophosmin in keratinocytes [148]. We suppose that PRINS is part of a ribonucleocomplex and its altered expression in psoriatic uninvolved epidermis contributes to the well-established aberrant stress response of psoriatic keratinocytes and as a consequence to psoriasis susceptibility.…”
Section: Discussionsupporting
confidence: 79%
“…Our data indicated that the elevated level of PRINS ncRNA in the psoriatic epidermis may contribute to psoriasis by disrupting signal transduction events mediating genes involved in apoptosis regulation such as G1P3 [148].…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…Therefore, we aimed at investigating (i) mRNA and protein expressions and activity of FAAH in human keratinocytes in Toll-like receptor (TLR)-induced inflammation models and (ii) the suggested anti-inflammatory effects of two newly developed, potent and selective N-alkylcarbamate FAAH inhibitors WOBE440 (IC 50 = 25 AE 8 nM) and WOBE479 (IC 50 = 78 AE 13 nM) (Fig. S1) which show high specificity over other known targets within the ECS [IC 50 > 10 lM for cannabinoid receptor (CNR)-1, CNR2, monoacylglycerol lipase and the putative endocannabinoid membrane transporter] (6) on primary (NHEK) and immortalized (HPV-KER) (7,8) human epidermal keratinocytes as well as in NC/Tnd mice, a widely used animal model of atopic dermatitis (AD) (9).…”
Section: Questions Addressedmentioning
confidence: 99%